Analysis and Design of Integrated Waste Disposal System Information Based on Website - Denny Gunawan; Hamzah Setiawan; Hindarto; Suprianto (SaNa: Journal of Blockchain, NFTs and Metaverse Technology, 2026)
This study aims to design a website-based information system for waste management at the Integrated Waste Processing Site (TPST) in Siwalanpanji Village, Sidoarjo Regency. This system is designed to facilitate the recording and analysis of waste data, including recycled waste and waste disposed of at the Waste Processing Site (TPS). The method used is Rapid Application Development (RAD), which includes the stages of planning needs, design, construction, and testing using Black Box Testing. The results of this study are expected to improve the efficiency of waste management and support better decision making in waste management in the village.